The clinical presentation, imaging features and differential diagnoses of congenital Wilms tumour. Issue 5 (30th May 2019) - Rampersad, Fidel; Diljohn, Jason; Goetz, Cristal
Abstract : Solid fetal renal masses are a rare finding on antenatal ultrasound, with hydronephrosis and cystic disease of the kidney usually being the most common causes for fetal renal enlargement. Herein we report a case of a solid fetal renal mass which was detected on third trimester antenatal ultrasound scanning. This renal mass was evaluated by MRI in the postnatal period and diagnosis confirmed by histological analysis, after surgical excision. Also discussed are the differential diagnoses and imaging features of other solid fetal renal masses, including congenital mesoblastic nephroma, nephroblastomatosis, renal sarcoma and angiomyolipoma.